1993
DOI: 10.1002/1097-0142(19930101)71:1<82::aid-cncr2820710114>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Papillary cystic tumors of the pancreas assessment of their malignant potential

Abstract: Background. Although the biologic characteristics of papillary cystic tumors (PCT) generally indicate a good prognosis, a malignant form has been reported. Methods. Twenty‐two examples of PCT were examined to assess their malignant potential by histologic, flow cytometric, and immunohistochemical studies. Results. Three had hepatic, peritoneal, and/or lymph node metastases (metastasizing tumors [MT]); the other 19 PCT had no such metastatic features (nonmetastasizing tumors [NMT]). Venous invasion was detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
148
2
17

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 239 publications
(175 citation statements)
references
References 26 publications
5
148
2
17
Order By: Relevance
“…[1][2][3][4][5][6] Attempts to separate aggressive from non-aggressive solid pseudopapillary neoplasms based on histologic criteria (such as vascular invasion, necrosis, increased mitotic rate, high nuclear grade) and size has yielded contradictory results with reports of histologically bland solid pseudopapillary neoplasms that have metastasized and histologically malignant solid pseudopapillary neoplasms with indolent outcomes. 4,7,8 Using morphologic features to predict the biological behavior of solid pseudopapillary neoplasms has limitations and is a major obstacle in stratifying patients into low-and highrisk groups as has been observed for other lesions, such as pheochromocytomas and neuroendocrine tumors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6] Attempts to separate aggressive from non-aggressive solid pseudopapillary neoplasms based on histologic criteria (such as vascular invasion, necrosis, increased mitotic rate, high nuclear grade) and size has yielded contradictory results with reports of histologically bland solid pseudopapillary neoplasms that have metastasized and histologically malignant solid pseudopapillary neoplasms with indolent outcomes. 4,7,8 Using morphologic features to predict the biological behavior of solid pseudopapillary neoplasms has limitations and is a major obstacle in stratifying patients into low-and highrisk groups as has been observed for other lesions, such as pheochromocytomas and neuroendocrine tumors.…”
mentioning
confidence: 99%
“…Both aneuploid and diploid tumors have been detected by flow cytometry. 3,6,[8][9][10][11] Various chromosomal abnormalities have also been reported, primarily using cytogenetic techniques. [12][13][14][15][16] Two studies using comparative genomic hybridization (CGH) found no chromosomal gains or losses, 11,17 while in another study of one case using the more sensitive array CGH technique, two alterations were detected: loss of heterozygosity for HRAS in chromosome band 11p15.5 and a less significant loss of the short arm of chromosome 16.…”
mentioning
confidence: 99%
“…Two tumors with metastatic disease were DNA aneuploid (3,4). However, the small number of patients does not allow a definitive conclusion on the prognostic validity of DNA cytometry.…”
Section: Discussionmentioning
confidence: 94%
“…Flow cytometric analyses have shown that most tumors are diploid (3,8,44), although focal aneuploidy may be found after extensive sampling (44). Two tumors with metastatic disease were DNA aneuploid (3,4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation